PENGARUH KUALITAS PELAYANAN TERHADAP KEPUASAN MASYARAKAT DALAM PELAKSANAAN TERA ULANG ALAT UKUR TAKAR TIMBANG DAN PERLENGKAPANNYA PADA BIDANG METROLOGI DI DINAS KOPERASI, USAHA MIKRO KECIL MENENGAH, PERINDUSTRIAN DAN PERDAGANGAN PROVINSI SULAWESI TENGAH - Usman, Hasrudin (Katalogis, 2013)
This research aimed to know the influence of Service Quality toward Society Satisfactory in Realization of UTTP Tool Calibration of Metrology Field at Department of Cooperatives and Small Industry Medium Enterorise and Trade Central Sulawesi Province. The theory of service quality used was from Zeithaml, Valarie A., A. Parasuraman and Leonard L. Berry which consist of tangible, reliability, responsiveness, assurance and empathy, whereas the theory of society satisfactory was from Philip Kotler which covers need, wants, and expectations. This research was a survey research with quantitative approach. The population of the research was the owner or the user of UTTP tool calibration that noted in calibration register book from October to November 2011 which numbered 120 persons that drawn using Taro Yamane formula so that the sample became 55 persons. The collection data method covered documentation study and questionnaire. The technique of data analysis used was simple linear regression analysis. The research result showed that there was an influence of service quality toward society satisfactory in UTTP tool calibration of Metrology Field at Department of Coopertives and Small Industry Medium Enterprise and Trade Central Sulawesi Province. This result also showed that the relationship between service quality and society satisfactory was on strong level. The variable descriptive analysis result of service quality showed that from all dimension, the assurance dimension has a strong result particularly on service efficiency assurance, whereas the weak dimension was tangible dimension which was the uncomfortable of service place.